Ethical Issues in the Music Industry Response to Innovation and Piracy - Easley, Robert F. (Journal of business ethics, 2005)
The current conflict between the recording industry and a portion of its customers who are involved in illicit copying of music files arose from innovations involving the compression and electronic distribution of files over the internet. This paper briefly describes some of the challenges faced by the recording industry, and examines some of the ethical issues that arise in various industry and consumer responses to the opportunities and threats presented by these innovations. The paper concludes by highlighting the risks associated with responses that threaten further innovation, ultimately reducing the chances of finding solutions that hold appeal for all parties.